PENGARUH WHISTLEBLOWING, BUDAYA, DAN RELIGIUSITAS TERHADAP PENCEGAHAN FRAUD ORGANISASI MAHASISWA: MORAL SEBAGAI MODERATOR - Khaira, Nurul; Aditiani, Clarisa May; Afifah, Annisa Nur (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2025)
Fraud in financial reporting in organisations often occurs. Fraudulent behaviour can harm the credibility and sustainability of an organisation. This study aims to determine the effect of whistleblowing system, organisational culture, and religiosity on fraud prevention in financial reporting of student organisations at Ahmad Dahlan University, individual morality as a moderating variable. The method of analysis used in this study is through analytical tests in the form of outer model and inner model and moderated regression analysis (MRA) by utilising SmartPLS 3.0 software. The results of this study indicate that first, the whistleblowing system has a positive effect on fraud prevention. Second, organisational culture has a positive effect on fraud prevention. Third, religiosity has no effect on fraud prevention. Fourth, individual morals are unable to moderate the relationship between the whistleblowing system, organisational culture and religiosity on fraud prevention. This research is expected to provide an overview of the influence of fraud behaviour in the financial reporting of student organisations. Keywords: whistleblowing, organisational culture, religiosity, fraud prevention